Does Crude Oil Market Efficiency Improve After the Lift of the U.S. Export Ban? Evidence From Time-Varying Hurst Exponent - Shao, Yinghui (Frontiers in Physics, 2020)
On 18 December 2015, the 40-year old U.S. crude oil export ban was repealed. Since then U.S. crude and oil producers were allowed to reach the global market. In this paper, we study if the crude oil market efficiency increases after the lift of the export ban via the Centered Detrending Moving average Analysis (CDMA) and the Detrended Fluctuation Analysis (DFA). We examine the time-varying market inefficiency from 2011 to 2020 with different rolling windows. The results indicate that WTI becomes inefficient after the lift in medium-term. Though in short and long-term, there is evidence for the improvement of the degree of market efficiency. Generally, the WTI market presents mixed efficiency behavior at different time horizons. In one-year window, the degree of efficiency on Brent decreased while there isn’t enough evidence to conclude that Brent market efficiency increased or decreased in medium and long term. In this sense, the lift of the ban might have significant impact on WTI but not on Brent.